PENGARUH PEMBERIAN OLAHAN KEDELAI (Glycinemax (L.) Merill) DALAM MENGURANGI GEJALA MENOPAUSE PADA WANITA KLIMAKTERIUM - Mardiyana, Mardiyana; Arisanti, Atika Zahria (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Menopause is a period of cessation of menstruation caused by a decrease in the hormones estrogen and progesterone causing several symptoms that occur such as night sweats, insomnia, hot flashes, anxiety, fatigue, depression, memory disorders (senility), urogenital symptoms, urinary disorders (dysuria), and painful intercourse (dyspareunia). This causes discomfort in climacteric women, to reduce the discomfort, processed soybeans can be given, where processed soybeans contain isoflavone compounds that can bind to the hormone estrogen so that it can reduce the discomfort caused. Article search is done with a database using “Google Scholar”. The keywords are “soybean”, “menopause”, “climacterium”. The results of the analysis of the article are that there are 5 articles that explain there is a significant relationship between the administration of processed soybeans in reducing menopausal symptoms in climacteric women.